2014
DOI: 10.1590/s0034-8910.2014048005214
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in cervical and breast cancer mortality in Brazil

Abstract: OBJECTIVE To analyze cervical and breast cancer mortality in Brazil according to socioeconomic and welfare indicators.METHODS Data on breast and cervical cancer mortality covering a 30-year period (1980-2010) were analyzed. The data were obtained from the National Mortality Database, population data from the Brazilian Institute of Geography and Statistics database, and socioeconomic and welfare information from the Institute of Applied Economic Research. Moving averages were calculated, disaggregated by capita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
101
1
58

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(165 citation statements)
references
References 17 publications
(21 reference statements)
5
101
1
58
Order By: Relevance
“…Survival estimates for cervical cancer have been hampered owing to the under-estimation of mortality due to this cancer. According to Girianelli et al (2014), the mortality rates for cervical cancer are in fact higher than those disclosed in the nation's Mortality Information System (SIM), if they are corrected by the death certificates that give ill-defined causes and, moreover, cases classified as deaths due to malignant neoplasm of the uterus, which are unspecified. According to Gamarra's study, after correction for ill-defined causes and the unspecified portion of the uterus, cervical cancer mortality rates have actually risen by no less than 103.4% for Brazil overall.…”
Section: Discussionmentioning
confidence: 99%
“…Survival estimates for cervical cancer have been hampered owing to the under-estimation of mortality due to this cancer. According to Girianelli et al (2014), the mortality rates for cervical cancer are in fact higher than those disclosed in the nation's Mortality Information System (SIM), if they are corrected by the death certificates that give ill-defined causes and, moreover, cases classified as deaths due to malignant neoplasm of the uterus, which are unspecified. According to Gamarra's study, after correction for ill-defined causes and the unspecified portion of the uterus, cervical cancer mortality rates have actually risen by no less than 103.4% for Brazil overall.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, three authors identified increased educational level as risk factor (Chart 2) 34,36,40 . Decreased educational level may explain increased risk of non-participation on screening programs and BSE in three out of four studies (Chart 2) 22,29,50 .…”
Section: Education and Income Were Context-dependent Risk Factors Of mentioning
confidence: 93%
“…In a Chilean study on the relationship between BC and malathion aerial spraying, Cabello et al extracted additional data on BC patients from medical records 47 . Three studies used databases instead of interviews (Chart 1) 35,36,50 . Most studies were case-control (N = 15) or cross-sectional (N = 10) (Chart 1).…”
Section: Methodological Approaches Differed Considerably Among Studiementioning
confidence: 99%
See 1 more Smart Citation
“…Histerectomia devido ao câncer: no rastreamento, o CCU microinvasivo pode ser detectado e tratado com a histerectomia extrafacial ou radical, indo para os estado de saúde "Histerectomizada (câncer)" ou realizar um procedimento onde há a preservação do colo (e.g., conização), que é o caso de mulheres que desejam manter a fertilidade, geralmente para mulheres com menos de 40 anos probabilidade de transição de infectado por HPV para câncer microinvasivo p 15,2 probabilidade de transição de infectado por HPV para câncer invasivo p 1, 3 probabilidade de transição de NIC I para suscetível p 3,3 probabilidade de NIC I permanecer como NIC I p 4,3 probabilidade de transição de NIC I para NIC II/III p 6,2 probabilidade de detectar e tratar NIC I (permanece por 1 ano em observação) p 5,4 probabilidade de NIC I permanecer em observação após 2 anos de lesão detectada e tratada p 1, 5 probabilidade de transição de NIC I para suscetível após 3 anos de lesão detectada e tratada p 6,6 probabilidade de NIC II/III permanecer como NIC II/III p 7,6 probabilidade de transição de NIC II/III para câncer microinvasivo p 9,6 probabilidade de detectar e tratar NIC II/III (permanece por 1 ano em observação) p 8,7 probabilidade de NIC II/III permanecer em observação após 2 anos de lesão detectada e tratada p 1, 8 probabilidade de transição de NIC II/III para suscetível após 3 anos de lesão detectada e tratada p 9,9 probabilidade de câncer microinvasivo permanecer como câncer microinvasivo p 10, 9 probabilidade de transição de câncer microinvasivo para câncer invasivo p 15,9 probabilidade de detectar e tratar câncer microinvasivo (permanece por 1 ano em observação) (até 39 anos) p 16,9 probabilidade de câncer microinvasivo permanecer em observação após 2 anos de lesão detectada e tratada p 11,10 probabilidade de câncer microinvasivo permanecer em observação após 3 anos de lesão detectada e tratada p ...…”
Section: Softwares Utilizadosunclassified